(untitled) (Homoeopathy for All, 2023)
Renal calculi, also called Kidney stones, a kidney stone is a hard, crystalline mineral material formed within the kidney or urinary tract. Kidney stones are a common cause of blood in the urine (hematuria) and often severe pain in the abdomen, flank, or groin. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.